Influence of electron-electron scattering on spin-polarized current states in magnetic wrapped nanowires - Gurzhi, R.N.; Kalinenko, A.N.; Kopeliovich, A.I.; Yanovsky, A.V.; Bogachek, E.N.; Landman, Uzi (Физика низких температур, 2003)
We study the role of electron-electron collisions in the formation of spin-polarized current states in a "spin guide" which is a system consisting of a non-magnetic conducting channel wrapped in the grounded nanoscale magnetic shell. It is shown that under certain conditions the spin guide may generate and transport over long distances the non-equilibrium electron density with a high level of spin polarization, even though the frequent electron-electron scattering leads to a common drift of non-equilibrium electrons. We also propose some ways to convert the spin-polarized electron density into a spin-polarized electric current.